PENERAPAN PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INTEGRATION OF READING AND COMPOSITION) UNTUK ENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN IRISAN DAN GABUNGAN DUA HIMPUNAN KELAS VII A SMP 1 ISLAMJEMBER SEMESTER GENAP TAHUN PELAJARAN 2013 - Khoroid, Mauhibatul; Trapsilasiwi, Dinawati; Setiawani, Susi (Department of Mathematics Education , University of Jember, 2013)
Abstract. The goals of this research were: (1) to describe the application of cooperative learning type CIRC; (2) to analyze the students’ activities; (3) to analyze the students’ achievement achievement at 7 A Islamic Junior High School Jember. The type of this research was Classroom Action Research. The research methodology of this study used Hopkins scheme model which is spiral shaped. Data collection method of this research used observation, documentation, interview, and test. The data analysis used: (1) the percentage of students learning activities; (2) the percentage of achievement. This research was done through two cycles and there was two meeting in every cycle. The percentage classically of achievement in first cycle was 26,67 %. The percentage of students achievement at second cycle was 86,67 %. Key Words : Students’ activities, Implementing of cooperative learning CIRC, Intersection and union of two sets